Recurrent transient visual loss in secretory carcinoid tumor - Vivian Paraskevi Douglas; Shahin Owji; Mohammad Pakravan; Chaow Charoenkijkajorn; Noor A.R. Laylani; Pamela Davila-Siliezar; Yingchao Piao; Andrew G. Lee (American Journal of Ophthalmology Case Reports)
Purpose: We describe a case of a 68-year-old woman who had a biopsy-proven carcinoid of the lung and transient episodes of unilateral and bilateral vision loss presumed to be the result to intermittent serum elevations of vasoactive peptides secondary to an occult carcinoid. Observations: A 68-year-old female with history of carcinoid tumor of the lung presented with multiple recurrent and alternating unilateral and bilateral transient vision loss (TVL) which were increasing in frequency over a period of one month. Ophthalmologic examination was unremarkable. Further investigations were significant for elevated levels of serum chromogranin A. Positron emission tomography (PET) showed no recurrent or metastatic carcinoid tumor until after 11 months of persisting symptoms along with increased serum chromogranin A levels where three carcinoid tumorlets were detected in the left lower pulmonary lobe. Conclusions and importance: Clinicians should be aware that TVL can be a manifestation of the vasoactive secretory products in patients with history of carcinoid tumor.